Dare to share - Ong, Yun Qi (Nanyang Technological University, 2021)
This paper presents Dare to Share, a communications campaign designed to encourage openness in male adolescents aged 14 to 17 towards seeking professional help for mental health issues. The campaign was initiated by four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Male adolescents have an aversion towards seeking help for issues related to mental health, due to an underlying fear of being seen as weak and vulnerable. As a result, many cases go undiagnosed, and the consequences have manifested in the rising trend of youth suicides. Based on formative research findings and the Theory of Reasoned Action (TRA), the team developed an integrated communications campaign seeking to reduce internalised stigma and peer stigma in order to encourage help-seeking behaviour. The campaign was fully digital, existing on both Instagram and Tik Tok—social media platforms frequented by male adolescents. Based on post-campaign evaluation results, the campaign achieved its attitudinal, behavioural and output objective targets. It also earned an estimated $114,000+ in PR value, an estimated combined reach of 245,004 across all social media platforms and 9,625 total social media engagements. The target audience who were exposed to the campaign showed an overall increase in (i) mental health resources, (ii) attitudes towards seeking help, decrease in (iii) internalised stigma, (iv) peer stigma, and an increase in (v) intention to adopt help-seeking behaviour and (vi) actual help-seeking behaviour. Dare to Share’s importance stemmed from it being the first mental health campaign to specifically target male adolescents in Singapore, an at-risk group that has often been left out of the mental health conversation. A discussion on the campaign’s implications, limitations, and sustainability is included at the end of this paper.